Nanoscale Metal−Organic Frameworks and Their Nanomedicine Applications - Zhao, Dan; Zhang, Wang; Wu, Zhi-Han; Xu, Hui (Frontiers in Chemistry, 2022)
Abundant connectivity among organic ligands and inorganic metal ions makes the physical and chemical characters of metal-organic frameworks (MOFs) could be precisely devised and modulated for specific applications. Especially nanoscale MOFs (NMOFs), a unique family of hybrid nanomaterials, with merits of holding the nature as the mainstay MOFs and demonstrating particle size in nanoscale range which enable them prospect platform in clinic. Adjustability of composition and structure allows NMOFs with different constituents, shapes, and characteristics. Oriented frameworks and highly porous provide enough space for packing therapeutic cargoes and various imaging agents efficiently. Moreover, the relatively labile metal-ligand bonds make NMOFs biodegradable in nature. So far, as a significant class of biomedically relevant nanomaterials, NMOFs have been explored as drug carriers, therapeutic preparation, and biosensing and imaging preparation owing to their high porosity, multifunctionality, and biocompatibility. This review provides up-to-date developments of NMOFs in biomedical applications with emphasis on size control, synthetic approaches, and surfaces functionalization as well as stability, degradation, and toxicity. The outlooks and several crucial issues of this area are also discussed, with the expectation that it may help arouse widespread attention on exploring NMOFs in potential clinical applications.